Melting curve analyses in the quantitative real-time polymerase chain reaction of methylated/non-methylated DNA toward the detection of oral cancer using gargle fluid - Yusaku Noma; Hayate Sawayama; Kouta Yamashiro; Keitaro Nishi; Haruka Yoshinaga; Ryota Takaoka; Tsuyoshi Sugiura; Tomonori Sasahira; Tomofumi Hamada; Yasuo Suda; Tatsuo Okui (Heliyon, 2025)
The early detection and early treatment of oral cancer are of paramount importance for improving the patients' prognoses. Our group previously reported a noninvasive test for oral cancer that uses a commercially available methylation-specific multiple ligation-dependent probe amplification (MS-MLPA) method, focusing on the DNA methylation of cells in gargle fluid. However, the conventional MS-MLPA method is complicated, costly, and thus difficult to use for screening and other health examinations. We therefore sought to develop a simple screening method for the diagnosis of oral cancer by conducting a melting curve analysis in a quantitative real-time polymerase chain reaction (qPCR). The assay was performed by a qPCR of DNA from the gargle fluid of 20 patients with oral cancer and 20 healthy control subjects in the training set. The use of these data for the genes BRCA2, CDH13, and MLH1 provided good diagnostic performance. We also applied the assay to a test set of gargle fluid from 10 patients with oral cancer and 10 control subjects, and the results demonstrated the reproducibility of the diagnostic performance. In light of these findings, we propose that this new method could become a noninvasive and convenient screening tool for the detection of oral cancer.